Gastrointestinal Polyposis in Cowden Syndrome. Issue 7 (August 2017) - Shaco-Levy, Ruthy; Jasperson, Kory W.; Martin, Katie; Samadder, N.J.; Burt, Randall W.; Ying, Jian; Bronner, Mary P.
Abstract : Goals: To further characterize the gastrointestinal manifestations of Cowden syndrome in clinically well-annotated patients to improve the diagnosis of this syndrome. Background: The gastrointestinal manifestations of Cowden Syndrome, an important heritable and multiorgan cancer syndrome, are not well defined. Proper diagnosis is essential for effective cancer surveillance and prevention in these patients. Study: Cowden patients with gastrointestinal polyps were selected for medical record and pathologic slide review. Results: Of 19 total patients, genetic testing revealed pathogenic PTEN mutations in 12. Pan-colonic (11-patients, 58%) and pan-gastrointestinal (8-patients, 42%) polyp distributions were common. Inflammatory (juvenile) polyps were the most common of the hamartomatous polyp (18 patients, 95%), along with expansive lymphoid follicle polyps (12 patients, 63%), ganglioneuromatous polyps (10 patients, 53%), and intramucosal lipomas (5 patients, 26%). The findings of 2 or more hamartomatous polyp types per patient emerged as a newly described and highly prevalent (79%) feature of Cowden syndrome. Ganglioneuromatous polyps, rare in the general population, and intramucosal lipomas, which may be unique to Cowden syndrome, should both prompt further evaluation. Colonic adenomas and adenocarcinomas were common; 10 patients (53%) had single and 3 (16%) had ≥3 adenomas, whereas 2 (11%) had colonic adenocarcinoma, strengthening the emerging association of colorectal cancer with Cowden syndrome. Conclusions: The clinical phenotypes and gastrointestinal manifestations in Cowden syndrome are quite variable but this series adds the following new considerations for this syndromic diagnosis: multiple gastrointestinal hamartomas, especially 2 or more hamartoma types, and any intramucosal lipomas or ganglioneuromas. These features should warrant consideration of Cowden syndrome.